Observation of oncohematologic patients by general pediatricians - S. R. Varfolomeyeva; D. Yu. Kachanov; M. M. Shneyder; K. V. Dobrenkov; T. V. Shamanskaya; Ye. V. Samochatova; A. G. Rumyantzev (Онкогематология, 2022)
For past decades there have been substantial changes in the therapy of oncohematologic diseases in children. Today, the treatment of this subset of patients is impossible without close cooperation between pediatric oncology/hematology professionals and general pediatricians. Authors underline the following critical steps in the management of oncohematologic patients necessarily requiring participation of general pediatricians: early diagnosis of malignancies, management of patients during their anti-tumor treatment, observation of patients in complete remissions after effective anti-tumor treatment, management of patents receiving palliative care, organization of hospices. Issues regarding prophylaxis and treatment of infectious complications in oncohematologic patients, use of growth factors, substitutive treatment with blood components and vaccination are reviewed.